Utilizing iron oxide (α-Fe2O3) nanoparticles synthesized from Fe(II) complexes for enhanced seed germination and growth: A sustainable approach to boosting agricultural productivity - Arsha P. Mohan; V.G. Viju Kumar; M.S. Meenukutty; V.G. Vidya (Next Nanotechnology)
The limited germination rate and early growth of crops pose a significant challenge to agricultural productivity, necessitating innovative solutions to enhance seed performance and plant development. This study investigates the impact of iron oxide nanoparticles, synthesized from three Fe(II) complexes, on the germination and growth of okra (Abelmoschus esculentus) seeds. The Fe(II) complexes were calcined at 500°C to produce iron oxide nanoparticles, which were characterized using UV-Visible spectroscopy, FT-IR, SEM-EDX, TEM, and PXRD. The analyses confirmed the formation of α-Fe2O3 nanoparticles with sizes ranging from 30 nm to 67 nm, exhibiting significant surface plasmon resonance and characteristic peaks for α-Fe2O3. Application of iron oxide nanoparticles at a concentration of 0.5 mM led to a significant increase in seed germination rate, reaching 95 % ± 2.1, compared to just 25 % ± 1.5 in the control group (p < 0.05, n = 3), indicating statistically significant improvement. Furthermore, seedlings treated with iron oxide nanoparticles exhibited a 2.9 cm increase in root length and a 9.2 cm increase in shoot length after 10 days of exposure under laboratory conditions. The fresh weight of iron oxide nanoparticles-treated seedlings was 42 % higher than that of the control group. These findings demonstrate that low concentrations of α-Fe₂O₃ nanoparticles can markedly enhance okra seed germination and early seedling growth, likely due to improved iron availability and antioxidant activity. This study highlights the potential of iron oxide nanoparticles as an effective nanomaterial for improving crop yields and supporting sustainable agricultural practices.